Identifying and validating immunological biomarkers in obstructive sleep apnea through bioinformatics analysis - En-hui Zhou; Tian-jiao Zhou; Xiao-ting Wang; Jing-yu Zhang; Jian Guan; Shan-kai Yin; Wei-jun Huang; Hong-liang Yi; Jian-yin Zou (Scientific Reports)
Abstract Obstructive sleep apnea (OSA) is a prevalent sleep disorder characterized by disrupted breathing patterns and dysfunctions in multiple organ systems. Although studies support a close correlation between OSA and immune function, the broader implications and specific manifestations remain unclear. Therefore, it is pressingly needed to identify potential immune-related markers and elucidate underlying immunological mechanisms of OSA. OSA-related datasets (GSE38792) and immune-related genes were downloaded from the GEO and ImmPort databases and intersected to obtain differentially expressed immune-related genes (DEIRGs). GO, KEGG, and GSEA were employed to explore the biological functions of DEIRGs. Immune cells and immune regulation were analyzed by CIBERSORT. The ROC curve was constructed to assess the accuracy of each DEIRG. The co-regulatory networks of transcription factors, microRNAs, and drugs were built using the NetworkAnalyst database and visualized by Cytoscape. The levels of DEIRGs in clinical samples were validated by RT-qPCR. GO, KEGG, and GSEA revealed that DEGs were mainly enriched in negative regulation of immune response and antigen processing and presentation in OSA. IL33, IL10RB, ANGPTL1, EIF2AK2, SEM1, IFNA16, SLC40A1, FCER1G, IL1R1, TNFRSF17, and ERAP2 were identified as DEIRGs among 175 differentially expressed genes in OSA. Memory B cells, mast cells resting, and dendritic cells resting were the predominant immune cells related to DEIRGs. The co-regulatory network contained 128 miRNAs, 40 transcription factors, and 172 drugs/compounds. Finally, IL33, EIF2AK2, IL10RB, and ANGPTL1 were also upregulated in clinical OSA samples. The present study identified potential immune-related biomarkers and systematically elucidated underlying immunological mechanisms of OSA. These findings provide novel insights into the diagnosis, mechanism research, and management strategies for future studies.